The Digital Cable TV Pricing Mechanism and the Consumer Preferences: the Survey in Taiwan - Kuo-Feng Tseng (International Telecommunications Society (ITS), 2019)
As the cable system accomplishing 100% digitalization in Taiwan, NCC (National Communications Commission) proposes an unbundled pricing mechanism to allow consumers to choose the cable television channels that they actually watch. This study conducted an online survey and 1358 effective questionnaires were completed to know their willing to pay for each channel. The results show that there is a negative slop of demand, lower price for more subscribers, but near three quarters to half of subscribers did not want to pay for the individual channel. The genres of lifestyle, foreign news and movies are the top preferences that consumers pay higher prices. Based on the results of the subscribers' willing to pay, most of the television channels could not survive in the a la carte pricing mechanism.
Keywords: 330